Surfing alone? The Internet and social capital: evidence from an unforeseeable technological mistake - Stefan Bauernschuster; Oliver Falck; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
Does the Internet undermine social capital or facilitate inter-personal and civic engagement in the real world? Merging unique telecommunication data with geo-coded German individuallevel data, we investigate how broadband Internet affects several dimensions of social capital. One identification strategy uses panel information to estimate value-added models. A second exploits a quasi-experiment in East Germany created by a mistaken technology choice of the state-owned telecommunication provider in the 1990s that still hinders broadband Internet access for many households. We find no evidence that the Internet reduces social capital. For some measures including children's social activities, we even find significant positive effects.
Keywords: Z13; J24; 330; internet; social capital; Internet; Breitbandkommunikation; Online-Netzwerk; Social Capital; Soziale Beziehungen; Deutschland; Neue Bundesländer